2011
DOI: 10.2133/dmpk.dmpk-10-nt-101
|View full text |Cite
|
Sign up to set email alerts
|

Regional Distribution of Drug-metabolizing Enzyme Activities in the Liver and Small Intestine of Cynomolgus Monkeys

Abstract: The cynomolgus monkey is an animal species widely used to study drug metabolism because of its evolutionary closeness to humans. However, drug-metabolizing enzyme activities have not been compared in various parts of the liver and small intestine in cynomolgus monkeys. In this study, therefore, drug-metabolizing enzyme activities were analyzed in the liver (the five lobes) and small intestine (six sections from the duodenum to the distal ileum). 7-Ethoxyresorufin O-deethylation, coumarin 7-hydroxylation, pacli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 29 publications
1
14
0
Order By: Relevance
“…After centrifugation at 1500g for 10 min, the supernatant or extract was analyzed by reverse-phase high-performance liquid chromatography with a fluorescence or UV detector. Metabolic assays using diclofenac and testosterone as substrates were carried out as described previously (Nakanishi et al, 2011). To estimate a correlation between drugmetabolizing enzyme activities and P450 amounts, linear regression analysis was performed using Origin7.5J software (OriginLab Corp., Northampton, MA).…”
Section: Methodsmentioning
confidence: 99%
“…After centrifugation at 1500g for 10 min, the supernatant or extract was analyzed by reverse-phase high-performance liquid chromatography with a fluorescence or UV detector. Metabolic assays using diclofenac and testosterone as substrates were carried out as described previously (Nakanishi et al, 2011). To estimate a correlation between drugmetabolizing enzyme activities and P450 amounts, linear regression analysis was performed using Origin7.5J software (OriginLab Corp., Northampton, MA).…”
Section: Methodsmentioning
confidence: 99%
“…From these samples, genomic DNA was prepared using the Puregene DNA isolation kit (Qiagen, Valencia, CA) according to the manufacturer's instructions. Microsome samples were prepared from the livers of 7 Indochinese cynomolgus macaques as described previously [11]. The study was reviewed and approved by the Institutional Animal Care and Use Committee of Shin Nippon Biomedical Laboratories, Ltd.…”
Section: Preparation Of Dna and Microsome Samplesmentioning
confidence: 99%
“…CYP3A content in small intestine was lower in cynomolgus monkey (21 pmol/mg protein) (Table 1) than in human (74 pmol/mg protein) (Paine et al 2006). A previous study reported that testosterone 6β-hydroxylation in small intestine (jejunum) is comparable in cynomolgus monkeys and humans (Nakanishi et al 2011). This could be attributable to the higher metabolic activity of CYP3A enzymes in cynomolgus monkeys compared to that in human (Iwasaki et al 2010).…”
Section: Discussionmentioning
confidence: 96%
“…Catalytic activities mediated by cynomolgus CYP2C9/19, such as tolbutamide methylhydroxylation, diclofenac 4′-hydroxylation, and S -mephenytoin 4′-hydroxylation, are much lower in small intestine than in liver (Nakanishi et al 2011). These results suggest that small intestine would make a small contribution to first-pass metabolism of CYP2C9/19-metabolized drugs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation